(untitled) (MMIT Proceedings, 2025)
In recent years, the Central Asian countries — Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan — have increasingly integrated the concept of the green economy into their national policies in response to global climate challenges. This paper analyzes the role and dynamics of foreign direct investment (FDI) in advancing green economy transitions across the region during the period of 2019–2024. The study focuses on renewable energy development, sustainable infrastructure projects, and cross-country investment trends. Using data from multilateral institutions and international indicators — such as the Environmental Performance Index (EPI), Green Growth Index (GGI), and Sustainable Development Goals (SDGs) — the paper applies a comparative and visual analytical approach